A three-dimensional ant colony algorithm for multi-objective ice routing of a ship in the Arctic area - Zhang, Chi; Zhang, Di; Zhang, Mingyang; Zhang, Jinfen; Mao, Wengang (Ocean Engineering, 2022)
The increasing shipping activities in the Arctic area pose challenges to a ship's safety and fuel saving in ice-covered waters. The optimal ship route planning can reduce the fuel consumption and navigation risk for ice-going ships in the Northeast Route. In this paper, a multi-objective ice routing model has been developed for searching optimal routes with two objectives, i.e., minimization of the fuel consumption and the total risk along a voyage, considering the time-varying ice data. Navigation risk is considered by applying a risk assessment model for Arctic navigation. A 3D-ACA (Three-Dimensional Ant Colony Algorithm) has been proposed and implemented in the developed ice routing model to make decisions on a ship's passing waypoints and sailing speeds along each waypoint. Finally, several case studies with different route planning objectives have been conducted to demonstrate the performance of the proposed model.